Insulating ceramic heat-conducting material as well as preparation method and application thereof

By using a combination of ceramic fiber and insulating silica gel, directional penetration of the ceramic fiber and online mixing processing solves the problems of insufficient performance of insulating ceramic thermal conductive materials and complicated preparation processes in the existing technology, and achieves high-performance, low-cost insulation. Ceramic thermally conductive materials are suitable for the heat dissipation needs of high-performance chips and electronic equipment.

CN119350853APending Publication Date: 2025-01-24HUNAN AIBI INTELLIGENT TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411611822.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to provide insulated ceramic thermal conductivity materials with low thermal resistance, high thermal conductivity, low resistivity, high breakdown voltage and good mechanical properties. The preparation process is complex and the cost is high, making it difficult to be suitable for industrial production.

Method used

Insulating ceramic thermal conductive material made of ceramic fiber and insulating silica gel with a mass ratio of 1:1 to 6. Ceramic fiber has high thermal conductivity and low thermal expansion coefficient. Insulating silica gel is used to fix the ceramic fiber and enhance its resistivity and insulation properties. Through directional penetration of ceramic fibers and online glue mixing technology, the thermal conductivity efficiency and stability of the material are improved.

Benefits of technology

It achieves low thermal resistance, high thermal conductivity, low resistivity, high breakdown voltage and excellent mechanical properties of insulating ceramic thermal conductive materials. It is suitable for 5G chips, electronics, communications and other fields, and has simple process and low cost, making it suitable for industrial production. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an insulating ceramic heat-conducting material as well as a preparation method and application thereof. The insulating ceramic heat-conducting material is mainly prepared from ceramic fibers and insulating silica gel in a mass ratio of 1: (1-6), the insulating silica gel is mainly prepared from a flame-retardant heat-conducting liquid pouring sealant, an organic silicon electronic pouring sealant and a diluent. The preparation method comprises the following steps: (1) feeding, glue spraying and glue scraping; (2) pressing and defoaming; (3) drying; (4) cutting; and (5) polishing, and removing glue by laser to obtain the insulating ceramic heat-conducting material. The insulating ceramic heat-conducting material is applied to the technical fields of 5G chips, electronics, communication, illumination, electric power, national defense, new energy, automobiles, industry, medical treatment or data centers as a heat-conducting interface material. The insulating ceramic heat-conducting material disclosed by the invention is low in thermal resistance, high in heat conductivity, low in resistivity, high in breakdown voltage, good in mechanical property and excellent in comprehensive performance. The method is simple in process, low in cost and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an insulating thermally conductive material and a preparation method and application thereof, and in particular to an insulating ceramic thermally conductive material and a preparation method and application thereof. Background Art

[0002] At present, as new communication technologies move towards full popularization, consumer electronic products are accelerating their development towards high power, high integration, thinness and intelligence. As indicators such as integration, power density and assembly density continue to rise, while the performance of electronic devices in the 5G era continues to improve, the working power consumption and heat generation are rising sharply. At this time, the heat generated by electronic devices accumulates and increases rapidly. In order to ensure that electronic components can still work normally with high reliability under the ambient temperature, timely heat dissipation capacity becomes an important limiting factor affecting their service life. Studies have shown that for every 2°C increase in the temperature of electronic devices, the reliability decreases by 10%; the lifespan when the temperature reaches 50°C is only 1 / 6 of that at 25°C; according to statistics, material failures caused by heat concentration in electronic devices account for 65% to 80% of the total failure rate. Therefore, how to achieve rapid heat dissipation in a limited space has become a key issue in the development of power and electronic equipment today.

[0003] Traditional thermal conductive materials such as metals, metal oxides and other metal materials can no longer meet the insulation and thermal conductivity requirements of some special occasions, such as the insulation and thermal conductivity of power tubes, integrated blocks, heat pipes, integrated circuits, and copper-clad boards widely used in the fields of battery shielding, electronic information, and thermal measurement technology. They cannot be used as thermal conductive insulation materials required for weapons and equipment, aerospace electronic equipment, motors, communications, electrical equipment, and instruments. Therefore, high thermal conductivity and insulation polymer composite materials are an indispensable key link in heat dissipation design, and their research and development are of great significance.

[0004] CN116922873A discloses a method for preparing a long fiber type thermally conductive gasket, its products and applications, the preparation method comprising the following steps: S01 select a plurality of parallel cylindrical rods, and tightly wind the long fibers back and forth between the cylindrical rods to form a planar fiber layer; S02 repeat step S01 to obtain a plurality of planar fiber layers; stack the plurality of planar fiber layers, and apply a silicone layer between adjacent planar fiber layers; S03 wait for the silicone to solidify, and then cut to obtain the thermally conductive gasket. However, although the thermal conductivity of the thermally conductive gasket prepared by stacking long fibers is improved compared to other products, the thermal resistance of the product is still high, and the packaging requirements of high-quality electronic products have not been completely met.

[0005] In summary, with the development of integration technology and assembly technology, the size of electronic components and logic circuits is getting smaller and smaller. It is necessary to use high thermal conductivity insulation materials with good heat dissipation to quickly transfer the heat of thermal components to heat dissipation equipment to ensure the normal operation of electronic equipment. Therefore, it is urgent to develop thermally conductive insulating polymer composite materials with low thermal resistance, high thermal conductivity, low resistivity, high breakdown voltage, good mechanical properties and excellent comprehensive performance to replace traditional polymer materials as thermal interface and packaging materials. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide an insulating ceramic thermal conductive material and its application with low thermal resistance, high thermal conductivity, low resistivity, high breakdown voltage, good mechanical properties and excellent comprehensive performance.

[0007] The technical problem to be further solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a preparation method of insulating ceramic thermal conductive material with simple process, low cost and suitable for industrial production.

[0008] The technical solution adopted by the present invention to solve its technical problems is as follows: an insulating ceramic thermal conductive material, the insulating ceramic thermal conductive material is mainly made of ceramic fiber and insulating silica gel in a mass ratio of 1:1 to 6 (more preferably 1:3 to 6); the insulating silica gel is mainly made of flame-retardant thermal conductive liquid potting glue, silicone electronic potting glue and diluent. Ceramic fiber has high thermal conductivity, low thermal expansion coefficient and resistivity, but if added in powder form, the thermal conductivity efficiency is greatly reduced due to the lack of guidance in the thermal conduction direction. Insulating silica gel is mainly used to fix ceramic fiber and shape it, which has little effect on the thermal conductivity of ceramic fiber and can also enhance the resistivity and insulation performance of ceramic fiber. The use of ceramic fiber and insulating silica gel in the above ratio can greatly ensure that the comprehensive performance of insulating ceramic thermal conductive material in thermal conductivity, insulation and other aspects is more excellent. Insulating silicone made of flame-retardant thermally conductive liquid potting glue, silicone electronic potting glue and diluent can prolong the curing time of the mixed silicone through a certain preparation method, so that there is more time for infiltration and defoaming of ceramic fibers during the material molding process. In the cured insulating silicone, the distribution of silicone and ceramic fibers is more uniform, with almost no mechanical windows such as bubbles, strong stability and high reliability.

[0009] Preferably, the insulating ceramic thermally conductive material is a sheet with a thickness of 0.2 to 3.0 mm.

[0010] Preferably, the ceramic fibers are directional and penetrate the upper and lower surfaces of the insulating ceramic thermal conductive material. The structure is more conducive to the heat transfer along the ceramic fibers in the shortest path, achieving the effect of rapid heat conduction. The directional penetration includes vertical penetration or penetration in the same angle direction, and vertical penetration is more preferred.

[0011] Preferably, the mass fraction of ceramic fiber in the insulating ceramic thermal conductive material is 15-55% (more preferably 18-35%). Under the above ratio, the thermal conductivity and insulation of the insulating ceramic thermal conductive material can be guaranteed to the maximum extent, and it can also ensure that it has a certain degree of softness, good mechanical properties, and can be folded and bent arbitrarily for use in different scenarios and equipment.

[0012] Preferably, the ceramic fiber is one or more of boron nitride fiber, aluminum nitride fiber or aluminum oxide fiber.

[0013] Preferably, the weight proportions of each component in the insulating silica gel are: 100 parts of flame retardant thermal conductive liquid potting glue, 15-30 parts of silicone electronic potting glue, and 3-8 parts of diluent. If only flame retardant thermal conductive liquid potting glue is used, the AB two-component catalytic reaction will be too intense during the mixing process, and the solidification will form, which has poor fluidity and poor penetration effect on ceramic fibers, and it is also difficult to achieve defoaming and degumming later.

[0014] Preferably, the average cross-sectional diameter of the ceramic fibers is 6 to 20 μm (more preferably 8 to 16 μm). Ceramic fibers with such diameters are more conducive to heat conduction, reduce heat accumulation inside them, and the pores between the ceramic fibers become smaller, further improving the thermal conductivity.

[0015] Preferably, the flame retardant heat-conducting liquid potting glue is prepared by mixing component A and component B at a mass ratio of 1:0.8 to 1.2 (more preferably 1:1) when used.

[0016] Preferably, in the flame retardant thermal conductive liquid potting glue, component A is a crosslinking agent component, and component B is a catalyst component. More preferably, the flame retardant thermal conductive liquid potting glue has a model of GN-7053, which is divided into component A and component B and is purchased from Chongqing Siliconing Technology Co., Ltd.

[0017] Preferably, the organosilicon electronic potting adhesive is prepared by mixing component A and component B at a mass ratio of 1:0.8 to 1.2 (more preferably 1:1) before use.

[0018] Preferably, in the organosilicon electronic potting glue, component A is a crosslinking agent component, and component B is a catalyst component. More preferably, the model of the organosilicon electronic potting glue is Hanlikang H6039A (component A) and Hanlikang H6039B (component B), purchased from Hunan Chuangjin Technology Co., Ltd.

[0019] Preferably, the diluent is a silica gel diluent.

[0020] Preferably, the insulating silica gel is mixed online when in use, specifically by mixing components A and B in the flame retardant thermal conductive liquid potting glue, components A and B in the organosilicon electronic potting glue, and a diluent at the same time. Mixing the flame retardant thermal conductive liquid potting glue, components A and B in the organosilicon electronic potting glue, and a diluent at the same time helps to slow down the excessive solidification of the silica gel and increase its fluidity.

[0021] Preferably, the mixing temperature is 15-25°C and the mixing time is 2-4 minutes. If the mixing time is too long, overheating will occur, causing the silicone to solidify too quickly. The appropriate mixing time ensures uniform mixing and avoids premature solidification.

[0022] The technical solution adopted by the present invention to further solve the technical problem is as follows: A method for preparing an insulating ceramic thermal conductive material comprises the following steps: (1) Loading, spraying and scraping: First, lay a layer of primer inside the mold, then lay a layer of ceramic fiber in a directional stack in the mold, and then spray a layer of insulating silicone obtained by online mixing. After ultrasonic vibration, scrape the glue and repeat the operation to obtain multiple layers of ceramic fiber infiltrated with insulating silicone. (2) Pressing and degassing: applying a flat plate pressure to the ceramic fiber impregnated with the multi-layer insulating silica gel obtained in step (1) for pressing, while simultaneously performing ultrasonic vibration, squeezing out the excess insulating silica gel and forming, and then performing vacuum degassing to obtain a formed ceramic fiber insulating silica gel material; (3) Drying: vacuum drying the shaped ceramic fiber insulation silica gel material obtained in step (2) to obtain a ceramic fiber insulation silica gel block; (4) Cutting: Cutting the ceramic fiber insulation silicone block obtained in step (3) to obtain a ceramic fiber insulation silicone sheet; (5) Grinding and laser debonding: The ceramic fiber insulating silicone sheet obtained in step (4) is firstly polished and then laser debonded to obtain an insulating ceramic thermal conductive material.

[0023] Preferably, in step (1), the directional stacking and laying refers to directional stacking and laying perpendicular to the conveying direction of the conveyor belt or at a certain angle to the conveying direction of the conveyor belt, and more preferably, the stacking and laying is perpendicular to the conveying direction of the conveyor belt.

[0024] Preferably, in step (1), the height of the multilayer ceramic fiber impregnated with insulating silicone is equivalent to 1.5 to 2.0 times the height of the target material. Since the natural stacking of ceramic fibers is too fluffy and is limited by the flow rate of silicone within a limited time, subsequent pressing and degassing is required to make the ceramic fibers more closely arranged and to initially squeeze out the bubbles in the gaps between the ceramic fibers. Therefore, in order to obtain a product with a qualified height, the height of the ceramic fiber impregnated with insulating silicone needs to be greater than the height of the target material.

[0025] Preferably, in step (1), the operation is repeated 60 to 100 times.

[0026] Preferably, in step (1), the frequency of the ultrasonic vibration is 20 to 40 kHz, and the duration of each time is 1 to 5 minutes. Ultrasonic vibration is more conducive to the uniform penetration of insulating silica gel into the gaps between ceramic fibers without changing the orderly arrangement of ceramic fibers.

[0027] Preferably, in step (2), the applied plate pressure is 0.05-0.10 MPa, and the pressing time is 3-5 min. Under the pressure and time, the ceramic fiber can be slowly pressed, and the excess insulating glue and some bubbles can be squeezed out.

[0028] Preferably, in step (2), the height after molding is equivalent to 1.1 to 1.5 times the height of the target material. The outer surface of the material after molding is uneven, and considering that subsequent degassing may cause the volume of the material to further shrink, the height after molding can be slightly higher than the target material height.

[0029] Preferably, in step (2), the frequency of the ultrasonic vibration is 20 to 40 kHz and the duration is 1 to 5 minutes. Ultrasonic vibration can squeeze out more bubbles during the pressing process, facilitating subsequent vacuum degassing.

[0030] Preferably, in step (2), the vacuum degassing temperature is room temperature, the vacuum degree is -0.08 to -0.10 MPa, and the time is 20 to 30 minutes. Since the insulating ceramic thermal conductive material after final cutting is relatively thin, even a tiny bubble may cause a hole in the material, seriously affecting its pass rate, and vacuum degassing can completely remove the bubbles in the insulating ceramic thermal conductive material as much as possible, thereby improving the stability and reliability of the material.

[0031] Preferably, in step (3), the temperature of the vacuum drying is 60 to 120°C, the vacuum degree is -0.08 to -0.10 MPa, and the time is 20 to 30 minutes. The purpose of vacuum drying is to accelerate the solidification of silica gel and shorten the product production cycle. If the temperature is too high, thermal expansion and contraction will cause hot air bubbles to re-enter the semi-solidified silica gel. If the time is too long, the production cost will increase.

[0032] Preferably, in step (4), the cutting is performed by cold cutting to a thickness of 0.2 to 3.0 mm. More preferably, the cutting is performed perpendicular to the direction in which the ceramic fibers in the ceramic fiber insulating silica gel block obtained in step (3) are stacked and laid.

[0033] Preferably, in step (5), the grinding speed is 4000-6000 r / min, and the grinding is performed until the surface is visually clean.

[0034] Preferably, in step (5), the laser head power of the laser debonding is 25 to 60 W.

[0035] The technical solution adopted by the present invention to further solve its technical problems is as follows: an application of an insulating ceramic thermally conductive material, which is used as a thermal interface material in technical fields such as 5G chips, electronics, communications, lighting, electricity, national defense, new energy, automobiles, industry, medical care or data centers. Consumer electronics and communication equipment are the most important downstream application areas of thermal interface materials, accounting for more than 80% in total; the miniaturization and high-power development of components in electrical and electronic equipment makes heat dissipation the key; my country's high-performance chips and high-heat components use 5 billion pieces of thermal conductive sheets and related materials every year, and the demand for insulating thermally conductive materials is huge, with a market size of 20 billion yuan, which may reach more than 50 billion yuan in the future.

[0036] The beneficial effects of the present invention are as follows: (1) The insulating ceramic thermal conductive material of the present invention has low thermal resistance and a thermal conductivity coefficient of up to 27W / mK. Its thermal conductivity is much higher than the 1.0-1.5W / mK of common domestic products, and also much higher than the 10-12W / mK of imported products from Europe and the United States and the 15W / mK of Shin-Etsu of Japan. However, the high-end insulating thermal conductive materials used by mainstream international and domestic manufacturers, such as Honeywell thermal grease, thermal phase change materials and Shin-Etsu insulating thermal conductive gaskets of Japan, have a thermal conductivity coefficient of only 7-8W / mK, and high-performance insulating thermal conductive materials are extremely scarce. The resistivity is low and the breakdown voltage is as high as 10kV. The insulation performance is much higher than that of current products on the market, while the mainstream market demand is below 6kV. The insulating ceramic thermal conductive material of the present invention has high thermal conductivity, superior insulation performance, good mechanical properties and excellent comprehensive performance. It will greatly reduce the performance degradation of high-performance chips due to insufficient heat dissipation, greatly improve chip performance, and make revolutionary contributions to the computing power and performance improvement of smart products in various fields. (2) The method of the present invention has simple process, low cost and is suitable for industrial production; (3) The insulating ceramic thermal conductive material of the present invention can be widely used in technical fields such as 5G chips, electronics, communications, lighting, electricity, national defense, new energy, automobiles, industry, medical care or data centers. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] The average cross-sectional diameter of the alumina fiber used in the embodiments of the present invention and the comparative examples is 10 μm and is commercially available. The average cross-sectional diameter of the aluminum nitride fiber is 10 μm and is commercially available. The model of the flame retardant and thermally conductive liquid potting glue is GN-7053, which is divided into component A (cross-linking agent component) and component B (catalyst component), and is purchased from Chongqing Si Ning Technology Co., Ltd.; the model of the silicone electronic potting glue is Hanlikang H6039A (component A, cross-linking agent component) and Hanlikang H6039B (component B, catalyst component), which are purchased from Hunan Chuangjin Technology Co., Ltd.; the raw materials or chemical reagents used in the embodiments of the present invention and the comparative examples, unless otherwise specified, are obtained through conventional commercial channels.

[0039] An insulating alumina thermal conductive material embodiment 1-1 to 1-6 The insulating alumina thermal conductive material is made of alumina fiber and insulating silicone in a mass ratio of 1:5; the insulating silicone is made of flame-retardant thermal conductive liquid potting glue, silicone electronic potting glue and silicone diluent; the insulating alumina thermal conductive materials are sheets with thicknesses of 0.2 mm, 0.3 mm, 0.5 mm, 1.0 mm, 1.5 mm and 2.0 mm (respectively referred to as Examples 1-1 to 1-6); the alumina fiber vertically penetrates the upper and lower surfaces of the insulating alumina thermal conductive material; in the insulating alumina thermal conductive material, the mass fraction of the alumina fiber is 21.3%; When the insulating silicone is used, online mixing is performed, and the specific method is: 50 parts by weight of component A and 50 parts by weight of component B in the flame retardant thermal conductive liquid potting glue, 12 parts by weight of component A and 12 parts by weight of component B in the silicone electronic potting glue, and 6 parts by weight of silicone diluent are mixed at 20° C. for 3 minutes.

[0040] A method for preparing an insulating alumina thermally conductive material Examples 1-1 to 1-6 (1) Loading, spraying and scraping: First, lay a layer of primer inside the mold, then stack and lay a layer of alumina fiber in the mold perpendicular to the conveying direction of the conveyor belt, and then spray a layer of insulating silica gel obtained by online mixing. Perform ultrasonic vibration at 30kHz for 2 minutes each time, then scrape the glue. Repeat the operation 80 times to obtain a 15.5 cm high multi-layer alumina fiber impregnated with insulating silica gel; (2) Pressing and degassing: applying a flat plate pressure of 0.06 MPa to the multi-layer alumina fiber impregnated with insulating silica gel obtained in step (1) for 4 min, pressing down to a height of 12.8 cm, and simultaneously performing ultrasonic vibration at 30 kHz for 2 min to squeeze out excess insulating silica gel and form it, and then performing vacuum degassing at room temperature and -0.09 MPa for 25 min to obtain a formed alumina fiber insulating silica gel material; (3) Drying: The molded alumina fiber insulating silica gel material obtained in step (2) is vacuum dried at 90° C. and −0.09 MPa for 25 min to obtain an alumina fiber insulating silica gel block; (4) Cutting: perpendicular to the direction in which the alumina fibers in the alumina fiber insulating silica gel block obtained in step (3) are stacked and laid, and cold cutting is performed to a thickness of 0.2 mm, 0.3 mm, 0.5 mm, 1.0 mm, 1.5 mm, and 2.0 mm, respectively, to obtain alumina fiber insulating silica gel sheets; (5) Grinding and laser debonding: The alumina fiber insulating silicone sheet obtained in step (4) was first grinded at a rotation speed of 5000 r / min until the visual surface was clean, and then laser debonding was performed under the condition of a laser head power of 50 W to obtain a 10.0 cm high insulating alumina thermal conductive material.

[0041] Application Example 1 of an Insulating Alumina Thermal Conductive Material The insulating alumina thermally conductive material is used as a thermally conductive interface material in the field of 5G chip technology.

[0042] Example 2 of an insulating alumina thermal conductive material The insulating alumina thermal conductive material is made of alumina fiber and insulating silicone in a mass ratio of 1:4; the insulating silicone is made of flame-retardant thermal conductive liquid potting glue, silicone electronic potting glue and silicone diluent; the insulating alumina thermal conductive material is a sheet with a thickness of 2.0 mm; the alumina fiber vertically penetrates the upper and lower surfaces of the insulating alumina thermal conductive material; in the insulating alumina thermal conductive material, the mass fraction of alumina fiber is 24.8%; When the insulating silicone is used, online mixing is performed, and the specific method is: 52 parts by weight of component A and 48 parts by weight of component B in the flame retardant thermal conductive liquid potting glue, 10 parts by weight of component A and 8 parts by weight of component B in the silicone electronic potting glue, and 6 parts by weight of silicone diluent are mixed at 22° C. for 3 minutes.

[0043] Example 2 of a method for preparing an insulating alumina thermally conductive material (1) Loading, spraying and scraping: First, lay a layer of primer inside the mold, then stack and lay a layer of alumina fiber in the mold perpendicular to the conveying direction of the conveyor belt, and then spray a layer of insulating silica gel obtained by online mixing. Perform ultrasonic vibration at 30kHz for 3 minutes each time, then scrape the glue. Repeat the operation 60 times to obtain a 12.8cm high multi-layer alumina fiber impregnated with insulating silica gel. (2) Pressing and degassing: applying a flat plate pressure of 0.08 MPa to the multi-layer alumina fiber impregnated with insulating silica gel obtained in step (1) for pressing for 5 minutes, pressing down to a height of 11.0 cm, and simultaneously performing ultrasonic vibration at 30 kHz for 3 minutes to squeeze out excess insulating silica gel and form it, and then performing vacuum degassing at room temperature and -0.08 MPa for 20 minutes to obtain a formed alumina fiber insulating silica gel material; (3) Drying: The molded alumina fiber insulating silica gel material obtained in step (2) is vacuum dried at 80° C. and −0.09 MPa for 20 min to obtain an alumina fiber insulating silica gel block material; (4) Cutting: perpendicular to the direction in which the alumina fibers in the alumina fiber insulating silica gel block obtained in step (3) are stacked and laid, cold cutting to a thickness of 2.0 mm to obtain an alumina fiber insulating silica gel sheet; (5) Grinding and laser debonding: The alumina fiber insulating silicone sheet obtained in step (4) was first grinded at a rotation speed of 4500 r / min until the visual surface was clean, and then laser debonding was performed under the condition of a laser head power of 40 W to obtain an 8.2 cm high insulating alumina thermal conductive material.

[0044] Application Example 2 of an Insulating Alumina Thermal Conductive Material The insulating alumina thermally conductive material is used as a thermally conductive interface material in the field of 5G chip technology.

[0045] Aluminum nitride ceramic thermal conductive material embodiment 3 The insulating aluminum nitride thermal conductive material is made of aluminum nitride fiber and insulating silicone in a mass ratio of 1:6; the insulating silicone is made of flame-retardant thermal conductive liquid potting glue, silicone electronic potting glue and silicone diluent; the insulating aluminum nitride thermal conductive material is a sheet with a thickness of 2.0 mm; the aluminum nitride fiber vertically penetrates the upper and lower surfaces of the insulating aluminum nitride thermal conductive material; in the insulating aluminum nitride thermal conductive material, the mass fraction of aluminum nitride fiber is 19.7%; When the insulating silica gel is used, online mixing is performed, and the specific method is as follows: the same as in Example 1.

[0046] Example 3 of a method for preparing an insulating aluminum nitride thermal conductive material (1) Loading, spraying and scraping: First, lay a layer of primer inside the mold, then stack and lay a layer of aluminum nitride fiber in the mold perpendicular to the conveying direction of the conveyor belt, and then spray a layer of insulating silica gel obtained by online mixing. After ultrasonic vibration at 40kHz for 2 minutes each time, scrape the glue, repeat the operation 90 times, and obtain 18.2cm high multi-layer aluminum nitride fiber impregnated with insulating silica gel; (2) Pressing and degassing: applying a flat plate pressure of 0.10 MPa to the multi-layer aluminum nitride fiber impregnated with insulating silica gel obtained in step (1) for 4 minutes, pressing down to a height of 14.0 cm, and simultaneously performing ultrasonic vibration at 40 kHz for 2 minutes to squeeze out excess insulating silica gel and form it, and then performing vacuum degassing at room temperature and -0.08 MPa for 30 minutes to obtain a formed aluminum nitride fiber insulating silica gel material; (3) Drying: The aluminum nitride fiber insulating silica gel material obtained in step (2) is vacuum dried at 100° C. and −0.08 MPa for 30 min to obtain an aluminum nitride fiber insulating silica gel block; (4) Cutting: perpendicular to the direction in which the aluminum nitride fibers in the aluminum nitride fiber insulation silicone block obtained in step (3) are stacked and laid, cold cutting to a thickness of 2.0 mm to obtain an aluminum nitride fiber insulation silicone sheet; (5) Grinding and laser debonding: The aluminum nitride fiber insulating silicone sheet obtained in step (4) was first grinded at a rotation speed of 5500 r / min until the visual surface was clean, and then laser debonding was performed under the condition of a laser head power of 50 W to obtain an insulating aluminum nitride thermal conductive material with a height of 11.0 cm.

[0047] Application Example 3 of an Insulating Aluminum Nitride Thermally Conductive Material The insulating aluminum nitride thermal conductive material is used as a thermal conductive interface material in the field of 5G chip technology.

[0048] An insulating aluminum oxide thermal conductive material and a preparation method thereof Comparative Example 1 The difference between the thermal conductive material of this comparative example and the thermal conductive material of Examples 1-6 is that the insulating alumina thermal conductive material is made of alumina fiber and insulating silica gel in a mass ratio of 1:8, and the mass fraction of the alumina fiber in the insulating alumina thermal conductive material is 14.3%. The rest is the same as Examples 1-6.

[0049] The preparation method of the insulating ceramic thermally conductive material of this comparative example is the same as that of method examples 1-6.

[0050] An insulating aluminum oxide thermal conductive material and a preparation method thereof Comparative Example 2 The difference between the thermal conductive material of this comparative example and the thermal conductive material of Examples 1-6 is that the insulating silica gel is mixed online when used, and the specific method is: 62 parts by weight of component A and 62 parts by weight of component B in the flame retardant thermal conductive liquid potting glue and 6 parts by weight of silica gel diluent are mixed at 20° C. for 3 minutes. The rest is the same as Examples 1-6.

[0051] The preparation method of the insulating ceramic thermally conductive material of this comparative example is the same as that of method examples 1-6.

[0052] An insulating aluminum oxide thermal conductive material and a preparation method thereof Comparative Example 3 The thermally conductive material of this comparative example is the same as the thermally conductive material embodiments 1-6.

[0053] The preparation method of the insulating alumina thermal conductive material in this comparative example is different from that of method examples 1-6 in that: in step (1), ultrasonic vibration is performed at 30 kHz for 1 min each time; in step (2), ultrasonic vibration is performed at 30 kHz for 1 min; and the vacuum degassing time is 15 min. The rest is the same as that of method examples 1-6.

[0054] In order to evaluate the thermal, insulation and mechanical properties of the insulating ceramic thermally conductive materials obtained in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3, the insulating ceramic thermally conductive materials obtained in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were cut into a size of 20 mm*20 mm for testing according to the following standards: the thickness was measured using a vernier caliper, mm; the thermal resistance was tested using ASTM-D5470, cm 2 ·K / W; thermal conductivity is tested by ASTM-D5470, W / mK; resistivity is tested by ASTM-D257, 10 14 Ω·cm; breakdown voltage is tested according to GB / T1695-2005, kV; compression rate is tested according to ASTM C165-2007, %; tensile strength is tested according to GB / T 528-2009, MPa; elongation at break is tested according to GB / T 528-2009, %; hardness is tested according to GB / T531.2-2009, HA; density is tested according to GB T 533-2008, kg / m 3 ; The results are shown in Table 1: Table 1 Thermal, insulation and mechanical properties of the insulating ceramic thermally conductive materials obtained in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3

[0055] As shown in Table 1, it can be seen from the thermal, insulation and mechanical properties of the insulating ceramic thermal conductive materials of Examples 1-1 to 1-6 of the present invention that with the increase of thickness, the thermal resistance and resistivity gradually decrease, and are as low as 0.20 cm 2 K / W and 3.8×10 14Ω·cm, thermal conductivity, breakdown voltage, tensile strength and elongation at break gradually increase, reaching 25W / mK, 9kV, 13.7MPa and 89% respectively, while compression rate, hardness and density remain unchanged; from the thermal, insulating and mechanical properties of the insulating ceramic thermal conductive material embodiments 2 and 3 of the present invention, it can be seen that when the ratio of ceramic fiber to insulating silicone is changed, the above properties will change accordingly; from comparative example 1, it can be seen that when the amount of insulating silicone is too high, the thermal, insulating and mechanical properties will all deteriorate; from comparative example 2, it can be seen that if only flame-retardant thermal conductive liquid potting glue is used alone, the AB two-component catalytic reaction will be too intense during the mixing process, and it can be formed by solidification, with poor fluidity, poor penetration effect on ceramic fiber, and subsequent degassing and degumming are also difficult to achieve; from comparative example 3, it can be seen that ultrasonic vibration and degassing time are too short, which will make it difficult for the glue to penetrate into the fiber, and more bubbles will remain, resulting in deterioration of thermal, insulating and mechanical properties.

Claims

1. An insulating ceramic thermally conductive material, characterized in that: The insulating ceramic thermally conductive material is mainly made of ceramic fiber and insulating silica gel in a mass ratio of 1:1 to 6; the insulating silica gel is mainly made of flame-retardant thermally conductive liquid potting glue, organic silicon electronic potting glue and a diluent.

2. The insulating ceramic thermally conductive material according to claim 1, characterized in that: The insulating ceramic thermally conductive material is a sheet with a thickness of 0.2 to 3.0 mm; the ceramic fibers are directionally penetrated through the upper and lower surfaces of the insulating ceramic thermally conductive material; in the insulating ceramic thermally conductive material, the mass fraction of the ceramic fibers is 15 to 55%; the ceramic fibers are one or more of boron nitride fibers, aluminum nitride fibers or aluminum oxide fibers.

3. The insulating ceramic thermally conductive material according to claim 1 or 2, characterized in that: The weight parts of each component in the insulating silica gel are: 100 parts of flame retardant thermal conductive liquid potting glue, 15-30 parts of organic silicon electronic potting glue, and 3-8 parts of diluent; the average cross-sectional diameter of the ceramic fiber is 6-20 μm; the flame retardant thermal conductive liquid potting glue is prepared by mixing component A and component B in a mass ratio of 1:0.8-1.2 when used; In the flame retardant heat-conducting liquid potting glue, component A is a crosslinking agent component, and component B is a catalyst component; the organosilicon electronic potting glue is prepared by mixing component A and component B in a mass ratio of 1:0.8 to 1.2 when in use; In the organic silicon electronic potting glue, component A is a cross-linking agent component, component B is a catalyst component; and the diluent is a silica gel diluent.

4. The insulating ceramic thermally conductive material according to claim 3, characterized in that: When the insulating silica gel is used, online mixing is performed, and the specific method is: component A and component B in the flame retardant thermal conductive liquid potting glue, component A and component B in the organic silicon electronic potting glue, and a diluent are mixed at the same time; the mixing temperature is 15-25° C., and the mixing time is 2-4 minutes.

5. A method for preparing the insulating ceramic thermally conductive material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Loading, spraying and scraping: First, lay a layer of primer inside the mold, then lay a layer of ceramic fiber in a directional stack in the mold, and then spray a layer of insulating silicone obtained by online mixing. After ultrasonic vibration, scrape the glue and repeat the operation to obtain multiple layers of ceramic fiber infiltrated with insulating silicone. (2) Pressing and degassing: applying a flat plate pressure to the ceramic fiber impregnated with the multi-layer insulating silica gel obtained in step (1) for pressing, while simultaneously performing ultrasonic vibration, squeezing out the excess insulating silica gel and forming, and then performing vacuum degassing to obtain a formed ceramic fiber insulating silica gel material; (3) Drying: vacuum drying the shaped ceramic fiber insulation silica gel material obtained in step (2) to obtain a ceramic fiber insulation silica gel block; (4) Cutting: Cutting the ceramic fiber insulation silicone block obtained in step (3) to obtain a ceramic fiber insulation silicone sheet; (5) Grinding and laser debonding: The ceramic fiber insulating silicone sheet obtained in step (4) is firstly polished and then laser debonded to obtain an insulating ceramic thermal conductive material.

6. The method for preparing the insulating ceramic thermally conductive material according to claim 5, characterized in that: In step (1), the height of the multi-layer ceramic fiber impregnated with insulating silica gel is equivalent to 1.5 to 2.0 times the height of the target material; the operation is repeated 60 to 100 times; the frequency of the ultrasonic vibration is 20 to 40 kHz, and the duration of each time is 1 to 5 minutes.

7. The method for preparing the insulating ceramic thermally conductive material according to claim 5 or 6, characterized in that: In step (2), the applied plate pressure is 0.05 to 0.10 MPa, and the pressing time is 3 to 5 minutes; the height after molding is equivalent to 1.1 to 1.5 times the height of the target material; the frequency of the ultrasonic vibration is 20 to 40 kHz, and the time is 1 to 5 minutes; the temperature of the vacuum degassing is room temperature, the vacuum degree is -0.08 to -0.10 MPa, and the time is 20 to 30 minutes.

8. The method for preparing the insulating ceramic thermally conductive material according to any one of claims 5 to 7, characterized in that: In step (3), the vacuum drying temperature is 60 to 120° C., the vacuum degree is -0.08 to -0.10 MPa, and the time is 20 to 30 min.

9. The method for preparing the insulating ceramic thermally conductive material according to any one of claims 5 to 8, characterized in that: In step (4), the cutting is cold cutting, and the cutting is performed to a thickness of 0.2 to 3.0 mm. In step (5), the grinding speed is 4000 to 6000 r / min, and the grinding is performed until the visual surface is clean. The laser head power of the laser degumming is 25 to 60 W.

10. An application of the insulating ceramic thermally conductive material as claimed in any one of claims 1 to 4, characterized in that: The insulating ceramic thermally conductive material according to any one of claims 1 to 4 is used as a thermally conductive interface material in the fields of 5G chips, electronics, communications, lighting, electricity, national defense, new energy, automobiles, industry, medical treatment or data center technology.